Relevansi Semiotika Dan Uṣhūl Fiqh: Telaah Atas Hadis-Hadis Aḥkām - Basayif, Muhammad Syamil (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Abstract The integration of semiotics as a modern analytical tool into the classical Islamic sciences is often limited to the discourse of ‘ulūm al-Qur'ān and ’ulūm al-hadīs. The themes discussed are only dominated by ethical discussions. However, uṣhūl fiqh plays an important role in analysing naṣ that relate to the jurisprudential-practical dimension. This article is a literature review that seeks to explore the relevance between Ferdinand de Saussure's semiotics and classical uṣhūl fiqh theory. The focus is on examining hadīths that contain legal-formal laws (hadīś ahkām). The question in this study is how the relevance between the two and how semiotics is implemented as a basis for the production of fiqh law (istinbāt al-ahkām). The main argument is that contemporary scientific paradigms do not necessarily contradict classical Islamic knowledge. However, differences in terminology and function are often considered as a gap between the two poles. The relevance of both appears especially in the concept of sign systems. This can be seen in how the uṣhūlīs assign new sign systems such as amr meaning obligatory and nahy meaning forbidden to naṣṣ. Integrating semiotics into uṣhūl fiqh will provide a new nuance in the treasury of Islamic knowledge. Keywords: Ferdinand de Saussure semiotics, Uṣhūl Fiqh, hadith ahkām. Abstrak Usaha mengintegrasikan semiotika sebagai pisau analisis modern ke dalam khazanah ilmu keislaman klasik kerap kali hanya berkutat pada diskursus ‘ulūm al-Qur’ān dan ‘ulūm al-hadīs. Tema yang dibicarakan pun hanya didominasi diskusi tataran dalam etis. Padahal selain keduanya, terdapat pula uṣhūl fiqh yang berperan penting dalam menganalisa naṣṣ yang berkaitan dengan dimensi yurisprudis–praksis. Artikel ini adalah kajian pustaka yang berusaha menelusuri relevansi antara semiotika Ferdinand de Saussure dengan teori uṣhūl fiqh klasik. Fokusnya adalah meneliti hadis-hadis yang bermuatan hukum legal-formal (hadīś ahkām). Pertanyaan dalam penelitian ini adalah bagaimana relevansi antara keduanya dan bagaimana semiotika diimplementasikan sebagai basis produksi hukum fikih (istinbāt al-ahkām). Argumen utamanya adalah bahwa tidak selamanya paradigma keilmuan kontemporer bertentangan dengan khazanah ilmu keislaman klasik. Hanya saja, perbedaan terminologi dan fungsi kerap kali dianggap sebagai jurang pemisah antara dua kutub tersebut. Relevansi keduanya nampak terutama dalam konsep sistem tanda. Hal ini bisa dilihat dari bagaimana para uṣhūlī memberikan sistem tanda baru seperti amr bermakna wajib dan nahy bermakna haram ke dalam naṣṣ. Mengintegrasikan semiotika ke dalam uṣhūl fiqh akan memberikan nuansa baru dalam khazanah ilmu Keislaman.